SYSTEM OF ACTIVITIES FOR THE LEARNING OF ORGANIC CHEMISTRY - Espinosa Fernández, Apolonio; Castillo Edua, Bertha Rita (Atenas, 2013)
The article comes up due to the need to give answer to one of the current problems in the higher university teaching: the learning of organic substances, for being this content the base to the study of Biochemistry. Objective, to prepare a system of activities for the study of the Organic Chemistry in Health Technology based on the use of the technologies of the information and communications with the use of the educational software “Molecule” for the developing learning, which facilitates to teachers and students an algorithm of work to encourage the learning of the content.